Evaluation of Immunoprotection Conferred by the Subunit Vaccines of GRA2 and GRA5 against Acute Toxoplasmosis in BALB/c Mice - Ching, Xiao T.; Fong, Mun Y.; Lau, Yee L. (Frontiers in Microbiology, 2016)
Toxoplasmosis is a foodborne disease caused by Toxoplasma gondii, an obligate intracellular parasite. Severe symptoms occur in the immunocompromised patients and pregnant women leading to fatality and abortions respectively. Vaccination development is essential to control the disease. The T. gondii dense granule antigen 2 and 5 (GRA2 and GRA5) have been targeted in this study because these proteins are essential to the development of parasitophorous vacuole (PV), a specialized compartment formed within the infected host cell. PV is resistance to host cell endosomes and lysosomes thereby protecting the invaded parasite. Recombinant dense granular proteins, GRA2 (rGRA2) and GRA5 (rGRA5) were cloned, expressed, and purified in Escherichia coli, BL21 (DE3) pLysS. The potential of these purified antigens as subunit vaccine candidates against toxoplasmosis were evaluated through subcutaneous injection of BALB/c mice followed by immunological characterization (humoral- and cellular-mediated) and lethal challenge against virulent T. gondii RH strain in BALB/c mice. Results obtained demonstrated that rGRA2 and rGRA5 elicited humoral and cellular-mediated immunity in the mice. High level of IgG antibody was produced with the isotype IgG2a/IgG1 ratio of ≈0.87 (p<0.001). Significant increase (p<0.05) in the level of four cytokines (IFN-γ, IL-2, IL-4 and IL-10) was obtained. The antibody and cytokine results suggest that a mix mode of Th1/Th2-immunity was elicited with predominant Th1-immune response inducing partial protection against T. gondii acute infection in BALB/c mice. Our findings indicated that both GRA2 and GRA5 are potential candidates for vaccine development against T. gondii acute infection.